The Influence of Feedback on Task-Switching Performance: A Drift Diffusion Modeling Account - Cohen Hoffing, Russell; Karvelis, Povilas; Rupprechter, Samuel; Seriès, Peggy; Seitz, Aaron R. (Frontiers in Integrative Neuroscience, 2018)
Task-switching is an important cognitive skill that facilitates our ability to choose appropriate behavior in a varied and changing environment. Task-switching training studies have sought to improve this ability by practicing switching between multiple tasks. However, an efficacious training paradigm has been difficult to develop in part due to findings that small differences in task parameters influence switching behavior in a non-trivial manner. Here, for the first time we employ the drift diffusion model to understand the influence of feedback on task-switching and investigate how drift diffusion parameters change over the course of task switch training. We trained 316 participants on a simple task where they alternated sorting stimuli by color or by shape. Feedback differed in 6 different ways between subjects groups, ranging from no feedback to a variety of manipulations addressing trial-wise vs block feedback, rewards vs punishments, payment bonuses and different payouts depending upon the trial type (switch/non-switch). While overall performance was found to be affected by feedback, no effect of feedback was found on task-switching learning. Drift Diffusion Modeling revealed that the reductions in RT switch cost over the course of training were driven by a continually decreasing decision boundary. Furthermore, feedback effects on RT switch cost were also driven by differences in decision boundary, but not in drift rate. These results reveal that participants systematically modified their task-switching performance without yielding an overall gain in performance.